2009
DOI: 10.1124/mol.109.057596
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-Mediated Stimulation of Tyrosine Hydroxylase mRNA Translation Is Mediated by Polypyrimidine-Rich Sequences within Its 3′-Untranslated Region and Poly(C)-Binding Protein 2

Abstract: Tyrosine hydroxylase (TH) plays a critical role in maintaining the appropriate concentrations of catecholamine neurotransmitters in brain and periphery, particularly during long-term stress, long-term drug treatment, or neurodegenerative diseases. Its expression is controlled by both transcriptional and post-transcriptional mechanisms. In a previous report, we showed that treatment of rat midbrain slice explant cultures or mouse MN9D cells with cAMP analog or forskolin leads to induction of TH protein without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…It was shown previously that the major function of cAMP is to modulate the transcription of target genes through the PKA-CREB pathway (64,72). However, there have been a few reports showing the cAMP-mediated regulation of translation; for example, it was shown previously that cAMP induces the mRNA translation of tyrosine hydroxylase in dopaminergic neurons (14,22,92). Here, we show that cAMP also has a positive effect on cap-dependent translation via the mTORC1 pathway.…”
Section: Discussionmentioning
confidence: 47%
“…It was shown previously that the major function of cAMP is to modulate the transcription of target genes through the PKA-CREB pathway (64,72). However, there have been a few reports showing the cAMP-mediated regulation of translation; for example, it was shown previously that cAMP induces the mRNA translation of tyrosine hydroxylase in dopaminergic neurons (14,22,92). Here, we show that cAMP also has a positive effect on cap-dependent translation via the mTORC1 pathway.…”
Section: Discussionmentioning
confidence: 47%
“…PCBP2 has also been demonstrated to play a role in translational regulation [16][17] as well as P-body and stress granule trafficking [29]. Therefore PCBP2 appears to be a coordinator/regulator of the major cytoplasmic processes involved in gene expression of select mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…In midbrain cultures, galanin was reported to cause a dramatic reduction in the number of TH + cells. This effect was only observed in cultures that had been previously exposed for several days to a lipophilic analog of cAMP (22), which stimulates TH expression (73). It may be concluded that galanin did not affect the survival of DA neurons but rather prevented the induction of the enzyme by the cyclic nucleotide in a population of DA neurons hyperpolarized by the peptide (22).…”
Section: Effect Of Inhibitory Neuromodulators On the Survival Of Sn Dmentioning
confidence: 99%